Архівні документи Кролевецького повіту 1918 р. як джерела з історії українського державотворення - Пластун, О.В. (Сіверщина в історії України, 2020)
На основі архівних джерел вводяться до наукового обігу дані
щодо перебігу подій на теренах Кролевеччини у період Української
Держави 1918 р. Проаналізувавши документи, пов’язані з діяльністю повітового коменданта та начальника господарчої частини
Кролевця, автор розширює локально-регіональний вектор дослідницьких робіт, присвячених Гетьманату Скоропадського – Української Держави 1918 р. Акцентована увага на наказах повітового коменданта, актах та телеграмах, що охоплюють період з
травня до серпня 1918 року.
Детального дослідження щодо історії Кролевецького району ча-
сів Української Держави у 1918 р. не проводилось. Ця розвідка, що
стане першим кроком у написанні всебічної наукової праці, особливо важлива для вивчення історії Сіверщини, оскільки в українській історіографії не існує комплексного дослідження з означеної тематики. The article is based on archival sources. It introduces into historical
circulation the data from Krolevechchyna in the period of the Ukrainian
State in 1918. Based on the analysis of the documents of this period related
to the activity of the county commandant and the head of the economical
sphere of Krolevets, the author extends the local vector of research dedicated
to the Hetmanate of Skoropadskyi - the Ukrainian State in 1918.
This period is important for modern historians in the context of studying
Ukrainian realities today. The archival base of the study must open up
a certain veil of the past, for it is this state-building during the Ukrainian
Revolution of 1917–1921 that is the least studied in terms of local history.
The author focuses on the orders of the county commandant, acts and
telegrams covering the period from May to August 1918.
There is no detailed study of the Krolevets district of the times of the
Ukrainian State in 1918, even a hundred years after its collapse. This
historical study will be the first step that will later turn into a comprehensive
regional history resesrch.
This work is especially important for Siverschyna, since the above
issues are rather unfinished, from the point of view of Ukrainian historiography
on this territory.